(untitled) (International Journal of Ayurveda and Pharma Research, 2023)
Infectious diseases are responsible for an immense global burden that impacts public health systems and economies worldwide, disproportionately affecting vulnerable populations. Its control and prevention relies on a thorough understanding of the factors determining transmission. Aparajitha Choornam is a classical Dhoopa yogam used by traditional Ayurvedic physicians since past for fumigation which prevents the spread of infectious fever and also disinfects the air from pathogens. It is highly effective in disinfecting living spaces during the seasonal spread of flu, chicken guinea, chicken pox, measles etc. Aparajitha vaporizer and azep spray are two modified form of Aparajitha dhoopachoornam prepared out of same ingredients that offers more user friendly and round the clock action. The present study compares the antibacterial activity of Aparajitha vaporizer and surface spray with Streptomycine in gram positive and gram negative bacteria and antifungal activity with Clotrimazole in Aspergillus niger and Candida albicans. The method used was Agar Disc Diffusion Method. The zones of inhibitions were calculated and its triplicate was done. To analyse the statistical data, one-way ANOVA and Dunnets tests were performed. The antibacterial activity of streptomycin and samples using Pseudomonas aeruginosa, Enterococcus faecalis, Staphylococcus aureus and streptococus mutans were found to be nearly same. Similarly antifungal activity of samples and clotrimazole as standard drug with aspergillus niger and with candida albicans were nearly same. The formulation of vaporizer and spray is purely herbal and thus it is beneficial to replace these with chemicals containing the same. The health benefits of these herbs were also got by using this herbal spray and vaporizer and can confidently use in the rooms of pregnant women, infants, old people etc. Thus this work gives a scientific validation of antimicrobial activity of Aparajitha vaporizer and surface spray which is more customer friendly.